Trends in Annual Mean, Maximum and Minimum Air Temperatures At Tripoli Airport, Shahat and Sebha (Libya): 1946-2010 - Ali, Abdalla Abdulhafid Milad (The Libyan Journal of Science, 2018)
Annual mean, annual mean maximum and annual mean minimum temperatures covering the period 1946-2010 at 3 locations in Libya have been analyzed to detect temporal and spatial patterns of long and short term trends. Over the long term period (1946-2010), the annual mean temperature has increased at every site, however the extent of mean temperature upward trend (warming) varied from region to region. The largest trend was found at Sebha followed by Tripoli Airport then Shahat. With respect to trends in maximum and minimum temperatures, the results showed that at northern sites annual mean minimum temperature has experienced more increase than that in the annual mean maximum temperature, whereas at south of Libya maximum temperature increased more than minimum temperature, although for Sebha station, they were comparable. For the short term period, 1991-2010, remarkable increasing trends (warming) were found in annual mean temperature at Tripoli airport and Sebha but for Shahat slight decreasing trend (cooling) was observed. Significant increasing trends occurred in the annual mean maximum temperature at the three regions, whereas for the annual mean minimum temperature increasing significant trends have been found at both North Western Region and Southern Region but for the North Eastern Region non-significant decreasing trend was observed.